Perbedaan rerata kadar protein-C pada sepsis neonatorum dengan kultur positif dan negative di RSUP H. Adam Malik Medan tahun 2018 - Jeffry Nugraha; Ricke Loesnihari; Guslihan Dasa Tjipta (DiscoverSys Inc., 2019)
Background: First ten months from conception is a period of susceptibility to infection. Diagnostic testing for disease must be conducted as quickly as possible for antimicrobial administration. Blood culture, the 'gold standard' for diagnosis, is full of shortcomings. Decreasing protein C levels are characteristic of sepsis due to an increase in consumption, degradation, or decreased synthesis, so that the onset of protein C deficiency may occur before the diagnosis of sepsis.Aim: The study aimed to determine the difference in mean serum C protein levels in septic neonatorum in which positive cultures compared with negative culturesMethods: The sample in this study were septic neonatorum patients in the perinatology unit of H. Adam Malik General Hospital Medan by consecutive sampling technique. The blood was incubated in BACTEC 9050 and identified with gram staining, gram-positive identified by catalase, coagulase and MSA tests, while gram-negative with API 20E. Protein C was examined with Coatron A4. A bivariate analysis determined differences in protein C in septic neonatorum with positive and negative cultures.Result: The prevalence of positive culture sepsis was 36.1%. The most common pathogens were Staphylococci epidermidis (19.4%). There was no significant difference in protein C levels between the septic neonatorum with positive and negative cultures (p = 0.166). Positive culture sepsis is a risk factor associated with protein C decreasing with p = 0.011. Positive culture sepsis had a higher risk of reducing protein C levels by 7.536 times compared to negative culture sepsis.Conclusion: There were no significant differences in protein C levels between septic neonatorum with positive and negative cultures, but sepsis was significantly associated with a decrease in C protein levels.